A broadly tuned odorant receptor in neurons of trichoid sensilla in locust, Locusta migratoria. (December 2016) - You, Yinwei; Smith, Dean P.; Lv, Mingyue; Zhang, Long
Abstract: Insects have evolved sophisticated olfactory reception systems to sense exogenous chemical signals. Odorant receptors (ORs) on the membrane of chemosensory neurons are believed to be key molecules in sensing exogenous chemical cues. ORs in different species of insects are diverse and should tune a species to its own specific semiochemicals relevant to their survival. The orthopteran insect, locust ( Locusta migratoria ), is a model hemimetabolous insect. There is very limited knowledge on the functions of locust ORs although many locust OR genes have been identified in genomic sequencing experiments. In this paper, a locust OR, LmigOR3 was localized to neurons housed in trichoid sensilla by in situ hybridization. LmigOR3 was expressed as a transgene in Drosophila trichoid olfactory neurons (aT1) lacking the endogenous receptor Or67d and the olfactory tuning curve and dose-response curves were established for this locust receptor. The results show that LmigOR3 sensitizes neurons to ketones, esters and heterocyclic compounds, indicating that LmigOR3 is a broadly tuned receptor. LmigOR3 is the first odorant receptor from Orthoptera that has been functionally analyzed in the Drosophila aT1 system. This work demonstrates the utility of the Drosophila aT1 system for functional analysis of locust odorant receptors and suggests that LmigOR3 may be involved in detecting food odorants, or perhaps locust body volatiles that may help us to develop new control methods for locusts. Graphical abstract: An odorant receptor, LmigOR3 is expressed in trichoid sensilla of locust ( Locusta migratoria ) and broadly tunes to odorants of C7 C10 ketones, C5 C8 esters and C5 C9 heterocyclics in antennal trichoid sensilla (aT1) of transgenic Drosophila . Highlights: Locust odorant receptor LmigOR3 is localized in chemosensory neurons of trichoid sensilla. LmigOR3 is strongly activated by some ketones, esters and heterocyclics, exhibiting a broad-tuning feature.